Anti-nucleolin aptamer AS1411: an advancing therapeutic - Van den Avont, Alexander; Sharma-Walia, Neelam (Frontiers in Molecular Biosciences, 2023)
Targeted therapy is highly desirable as it allows for selective cytotoxicity on diseased cells without off-target side effects. Nucleolin is a remarkable target for cancer therapy given its high abundance, selective presence on the plasma membrane, and multifaceted influence on the initiation and progression of cancer. Nucleolin is a protein overexpressed on the cell membrane in many tumors and serves as a binding protein for several ligands implicated in angiogenesis and tumorigenesis. Nucleolin is present in the cytoplasm, nucleoplasm, and nucleolus and is used by selected pathogens for cell entry. AS1411 is a guanosine-rich oligonucleotide aptamer that binds nucleolin and gets internalized in the tumor cells. AS1411 is well tolerated at therapeutic doses and localizes to tumor cells overexpressing nucleolin. AS1411 has a good safety profile and efficacy in relapsed acute myeloid leukemia and renal cell carcinoma with mild or moderate side effects. The promising potential of AS1411 is its ability to be conjugated to drugs and nanoparticles.When a drug is bound to AS1411, the drug will localize to tumor cells leading to targeted therapy with fewer systemic side effects than traditional practices. AS1411 can also be bound to nanoparticles capable of detecting nucleolin at concentrations far lower than lab techniques used today for cancer diagnosis. AS1411 has a promising potential to change cancer diagnoses and treatment.